Pemberian Jus Semangka terhadap Penurunan Tekanan Darah Penderita Hipertensi Usia Dewasa Muda - Nurjannah Nurjannah (Sarana Ilmu Indonesia (salnesia), 2020)
The incidence of hypertension in Southeast Sulawesi tends to increase each year. Many people with hypertension are tired of taking blood pressure-lowering drugs because they are addictive and have side effects. The objective of the study was to understand the effect of watermelon juice supplementation to decrease blood pressure on early adult hypertension sufferers in the working area of the Public Health Center of Poasia Kendari city. This study was a true experiment through pretest-posttest with a control group design. The sample size was 30 people who were determined by purposive sampling technique and was allocated by matching within 15 people for both treatment and control groups. The statistical test result showed that there were different blood pressure both systolic and diastolic blood pressures before and after receiving watermelon juice supplementation for 7 days with the dose was twice 350/gr/glass/day on treatment group with significance value ? = 0,000 (? = 0,05). Meanwhile, for the control group, there was no different blood pressure before and after receiving supplementation with significance value ? = 1,000 (? = 0,05) for systolic pressure and ? = 0,499 for diastolic one. There was different blood pressure after receiving watermelon juice supplementation between treatment and control groups with significance value ? =0,031 (? = 0,05) for systolic pressure and p = 0,012 for diastolic one. Hence, it’s concluded that there was a significant effect of watermelon juice supplementation to decrease the blood pressure on early adult hypertension sufferers.